Regional Development Strategy ("Journal "U". Economy. Management. Finance.", 2020)
In this article, the author presents an analysis of strategic planning in the context of the functioning of the modern economy. The use of modern management technologies implemented for the successful development of subjects is considered.
Keywords: region; strategy; regional development; management; regional planning; socio-economic development